Systematic review and meta-analysis of laparoscopy-assisted and open total gastrectomy for gastric cancer - Chen, Ke (Baishideng Publishing Group Co., Limited, 2013)
AIM: To evaluate the safety and efficacy of laparoscopy-assisted total gastrectomy (LATG) and open total gastrectomy (OTG) for gastric cancer. METHODS: A comprehensive search of PubMed, Cochrane Library, Web of Science and BIOSIS Previews was performed to identify studies that compared LATG and OTG. The following factors were checked: operating time, blood loss, harvested lymph nodes, flatus time, hospital stay, mortality and morbidity. Data synthesis and statistical analysis were carried out using RevMan 5.1 software. RESULTS: Nine studies with 1221 participants were included (436 LATG and 785 OTG). Compared to OTG, LATG involved a longer operating time [weighted mean difference (WMD) = 57.68 min, 95%CI: 30.48-84.88; P < 0.001]; less blood loss [standard mean difference (SMD) = -1.71; 95%CI: -2.48 - -0.49; P < 0.001]; earlier time to ﬂatus (WMD= -0.76 d; 95%CI: -1.22 - -0.30; P < 0.001); shorter hospital stay (WMD = -2.67 d; 95%CI: -3.96 - -1.38, P < 0.001); and a decrease in medical complications (RR = 0.41, 95%CI: 0.19-0.90, P = 0.03). The number of harvested lymph nodes, mortality, surgical complications, cancer recurrence rate and long-term survival rate of patients undergoing LATG were similar to those in patients undergoing OTG. CONCLUSION: Despite a longer operation, LATG can be performed safely in experienced surgical centers with a shorter hospital stay and fewer complications than open surgery.